2018
DOI: 10.1002/ar.23803
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of Digit‐Length Ratio in a Viviparous Lizard: Influence of Age, but not Preservation State or Sex of Interuterine Twin

Abstract: The existence of sex differences in digit-length ratio (especially between the second and fourth digits, 2D:4D) is well established for humans from fetal life onwards, and has been linked with later performance. In rodents, the ratio is affected prenatally by exposure to androgens and estrogens, with some research suggesting an influence from sex of the neighbouring intrauterine fetus. However, the ubiquity and ontogenetic development of sexual dimorphism in digit ratios is not well established among wild amni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
(154 reference statements)
0
13
0
Order By: Relevance
“…The use of various limbs digit ratios (2D:3D, 2D:4D and 3D:4D) in presented research poses a greater challenge in comparing the results (see in Introduction); this issue should be kept in mind for the purpose of designing future experiments. In addition to contributing to the advance of knowledge concerning digit ratios in Squamata, the necessity of which has been raised by numerous authors (Rubolini et al, 2006;Gomes and Kohlsdorf, 2011;Tobler et al, 2011;Van Damme et al, 2015;Woodhead et al, 2018), our results also provide new insights into the relationship between digit ratios and caudal autotomy. However, it should be emphasised that autotomy is a complex feature and tail damage is likely to be repeated throughout the life of a specimen, and the probability of keeping the tail intact decreases with age (Bustard and Hughes, 1966).…”
Section: Con Clus Ionmentioning
confidence: 57%
See 3 more Smart Citations
“…The use of various limbs digit ratios (2D:3D, 2D:4D and 3D:4D) in presented research poses a greater challenge in comparing the results (see in Introduction); this issue should be kept in mind for the purpose of designing future experiments. In addition to contributing to the advance of knowledge concerning digit ratios in Squamata, the necessity of which has been raised by numerous authors (Rubolini et al, 2006;Gomes and Kohlsdorf, 2011;Tobler et al, 2011;Van Damme et al, 2015;Woodhead et al, 2018), our results also provide new insights into the relationship between digit ratios and caudal autotomy. However, it should be emphasised that autotomy is a complex feature and tail damage is likely to be repeated throughout the life of a specimen, and the probability of keeping the tail intact decreases with age (Bustard and Hughes, 1966).…”
Section: Con Clus Ionmentioning
confidence: 57%
“…In the case of 2D:3D, detected differences between sexes were characterised by a high degree of variability among species. For example, in adult Otago/Southland geckoes Woodworthia, K E Y W O R D S caudal autotomy, Lacertidae, morphology, reptiles, sexual dimorphism, squamata significant sexual dimorphism in 2D:3D (with this ratio being higher in males) was found only in the right hindlimb (Woodhead et al, 2018), in Podarcis siculus only in the left hindlimb (Van Damme et al, 2015). In Podarcis muralis male had larger 2D:3D ratio on the left side than females, whereas in Mabuya planifrons males had lower 2D:3D ratios than females (Rubolini et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be remembered that the lack of differences between sexes in the digit ratio may be a byproduct, or, in a case where individuals occupy different habitats, the result of natural selection (see Introduction, as well as [ 30 ]). Finally, digit ratio measurements may be susceptible to artificial variation resulting from the accuracy of the methods used or the condition of the preserved individuals [ 26 , 46 , 47 ]. [ 26 ] suggested that the differences in the results of the two studies on O. pumilio were related to differences in the measurement methodology adopted, i.e., hand calipers versus software analysis of digital photographs.…”
Section: Discussionmentioning
confidence: 99%